2016
DOI: 10.3390/risks4010008
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Insurance for a Minimal Expected Retention: The Case of an Ambiguity-Seeking Insurer

Abstract: Abstract:In the classical expected utility framework, a problem of optimal insurance design with a premium constraint is equivalent to a problem of optimal insurance design with a minimum expected retention constraint. When the insurer has ambiguous beliefs represented by a non-additive probability measure, as in Schmeidler, this equivalence no longer holds. Recently, Amarante, Ghossoub and Phelps examined the problem of optimal insurance design with a premium constraint when the insurer has ambiguous beliefs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Amarante and Ghossoub [2] study the problem of optimal insurance design with a retention constraint and in the presence of the nonnegativity constraint on indemnities, but with ambiguity only on the side of the insurer, represented by a distortion T 2 of the probability measure P . Ghossoub [24] extends the setting of Amarante and Ghossoub [2] to also account for ambiguity on the side of the DM, represented by a distortion T 1 of the probability measure P . He shows that the optimal indemnity is a variable deductible schedule, with a state-contingent deductible that depends on the sate of the world only through T 1 and T 2 .…”
Section: Mario Ghossoubmentioning
confidence: 99%
See 3 more Smart Citations
“…Amarante and Ghossoub [2] study the problem of optimal insurance design with a retention constraint and in the presence of the nonnegativity constraint on indemnities, but with ambiguity only on the side of the insurer, represented by a distortion T 2 of the probability measure P . Ghossoub [24] extends the setting of Amarante and Ghossoub [2] to also account for ambiguity on the side of the DM, represented by a distortion T 1 of the probability measure P . He shows that the optimal indemnity is a variable deductible schedule, with a state-contingent deductible that depends on the sate of the world only through T 1 and T 2 .…”
Section: Mario Ghossoubmentioning
confidence: 99%
“…All the results of this section would still hold, with adequate modifications. Moreover, the assumption of absolute continuity of Q with respect to P can be dropped, and one can use the technique developed in Ghossoub [23,26] and Amarante and Ghossoub [2], based on a Lebesgue decomposition of P with respect to Q.…”
Section: Supmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Heilpern, [10] the CI-FM can be applied to many real decision-making cases in economics and business. It is also reported that CI-FM has been used in specific areas such as insurance [11], green building [12], airline services [13], business education evaluation [14], loan market matching [15], and financial risk [16]. In customer service-oriented research, Pasrija and Srivastava [17] investigated the software quality using the CI-FM.…”
Section: Introductionmentioning
confidence: 99%